Réponses

2012-12-01T18:08:56+01:00

Bonjour,


B=9(x-1)²-(x+4)²= c'est une indentité remarquable de la forme a²-b²=(²+b)(a-b)


B=(3(x+1)-x-4)(3(x+1)+x+4)=(3x+3-x-4)(3x+3+x+4)=


B=(2x-1)(4x+7)


D=9x²-1+(x+2)(3x-1)+(9x²-6x+1)


9x²-1=(3x+1)(3x-1)


(9x²-6x+1)=(3x-1)²


D=(3x+1)(3x-1)+(x+2)(3x-1)+(3x-1)²


D=(3x+1)(3x-1)+(x+2)(3x-1)+(3x-1)²


D=(3x-1)(3x+1+x+2+3x-1)=


D=(3x-1)(7x+4)


J'espère que tu as compris


A+



2012-12-01T18:40:48+01:00

Bonjour,

 

B=9(x-1)²-(x+4)²= c'est une indentité remarquable de la forme a²-b²=(²+b)(a-b)

 

B=(3(x+1)-x-4)(3(x+1)+x+4)=(3x+3-x-4)(3x+3+x+4)=

 

B=(2x-1)(4x+7)

 

D=9x²-1+(x+2)(3x-1)+(9x²-6x+1)

 

9x²-1=(3x+1)(3x-1)

 

(9x²-6x+1)=(3x-1)²

 

D=(3x+1)(3x-1)+(x+2)(3x-1)+(3x-1)²

 

D=(3x+1)(3x-1)+(x+2)(3x-1)+(3x-1)²

 

D=(3x-1)(3x+1+x+2+3x-1)=


D=(3x-1)(7x+4)

 

J'espère que tu as compris

j'espére voux avoir aider